(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
MongoDB, a document-oriented NoSQL database, is crucial in modern web applications, particularly in the MEAN (MongoDB, Express.js, Angular, Node.js) stack. The challenge with optimizing MongoDB schemas exists because of the no-schema database design approach combined with changing workload requirements. This article investigates the optimal approaches to creating and optimizing MongoDB schema designs. It focuses on normalization and denormalization decisions using shard and replication systems with workload-related optimizations and scale-up capabilities. The article evaluates modern AI schema optimization trends and computerized performance optimization that dramatically boosts operational efficiency across extensive applications. MEAN applications will obtain superior scalability, reduced query delays, and enhanced system performance through these implementation methods. When merged with reliable data protection and schema longevity, the article will provide organizations with a complete mold to optimize MongoDB schemas for peak operational efficiency.